Vitamin supplementation: unmonitored prescription can be dangerous. (31st July 2013) - Kumar, Naveen; Sharma, Sourabh; Gupta, Harish; Gadpayle, Adesh Kumar
Abstract : A 75-year-old illiterate woman presented with severe dehydration and altered sensorium. Investigations revealed severe hypercalcaemia with deranged renal function. ECG showed changes of hypercalcaemia and hypokalaemia. Since the patient was aged and had an acute presentation, malignancy was considered as the probable aetiology. Following prompt supportive treatment, she regained consciousness on the second day of admission. Later on, she provided a history of daily intake of vitamin D3 (cholecalciferol) sachet (60 000 IU/sachet) for the last 2 weeks, which had actually been prescribed to be taken once per week. Further investigation revealed very high levels of serum vitamin D. This case has been presented to reiterate the importance of known, but often overlooked facts: ECG can provide an important clue regarding the underlying metabolic encephalopathy; mega-dose supplementation of these seemingly innocuous vitamins should be monitored; and treatment regimes should be properly explained and monitored in elderly people.